Is motivational interviewing an effective intervention for improving the behaviour of targeted primary aged pupils? - Mahon, Charlotte (2016)
Motivational Interviewing (MI) is a treatment approach which over the last 25 years has received increasing evidentiary support. In recent years efforts have been made to explore the effectiveness of MI in educational settings. Research has highlighted favourable outcomes in terms of increasing academic achievement (Strait, Smith, McQuillin, Swan and Malone, 2012, Terry, Strait, McQuillin and Smith, 2014),reducing levels of obesity (Flattum, Friend, Neumark-Sztainer and Story (2009) and improving teacher-student interactions (Wells, Jones and Jones, 2015) in secondary and higher education settings. However, a literature search revealed that only one published study, (Atkinson and Cryer, 2015) adopting a case study methodology, has investigated the use of MI with Primary aged pupils.